Making sense of FMF while smoke is still blowing - Shay, Suellen (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Booysen, Susan (ed) (2015) Fees must fall: Student revolt, decolonization and governance in South Africa. Johannesburg: Wits University Press. ISBN 978-1-86814-985-8 pbk. Pages ix + 350. Susan Booysen, author and editor, of Fees must fall sets out to answer the key questions: what did the student revolt of late 2015 to mid-2016 mean for governance in South Africa? How did it affect higher education and national government? Booysen states clearly that the answers to these questions “depend on the lenses worn and the directed angle” but she argues in conclusion that “from whichever angle it is approached …. it is evident that governance in South Africa and its higher education institutions has been irrevocably altered” (p 310).